The Influence Of Work Ethic And Organizational Culture On Organizational Commitment Of Civil Servants In Pemangkat Community Health Center Sambas Regency - Istiqomah Istiqomah; Irfan Mahdi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the Influence of Work Ethic and Organizational Culture on the Organizational Commitment of Civil Servants at the Pemangkat Health Center, Sambas Regency. The methodology of this study uses a quantitative method with an associative research design. Data collected through questionnaires and interviews with 46 Civil Servants of the Pemangkat Health Center, Sambas Regency, West Kalimantan Province in 2024, saturated sampling the variables studied are Work Ethic (X1), Organizational Culture (X2) and Organizational Commitment (Y). Data analysis includes validity test, reliability test, classical assumption test (normality and linearity), multicollinearity test, multiple linear regression analysis, correlation coefficient, and determination, simultaneous influence test (F-test), and partial influence test (T-test). Based on the results of the simultaneous test (F-test), it shows that Work Ethic (X1) and on Organizational Commitment (Y). The results of the partial test (T-Test) show that Work Ethic (X1) and Organizational Culture (X2) separately have a positive and significant effect on Organizational Commitment (Y).